KAJIAN KONSEPSI PENGEMBANGAN ZONA EKONOMI MARITIM DI WILAYAH KEPULAUAN RIAU - Ronaldy Lovina (Jurnal Potensi, 2023)
Islands located and scattered in the Riau Archipelago Province must be built evenly and proportionally so as not to cause inequality in growth. Therefore, it is necessary to have a conception of coastal area development based on archipelego. The results of the Location Quotion analysis in each region, there is a dominance of 9 (nine) superior/base sectors in the Batam Bintan and Karimun areas as well as in Tanjungpinang City (BBK) and 10 (ten) leading/base sectors in the Natuna Anambas and Lingga areas ( NAL) which is the main source of regional income based on Gross Regional Domestic Revenue (GRDP) for business fields. By looking at the direction of development and development orientation, it is necessary to build an economic system that can focus development on the maritime sector, agriculture sector, agropolitan and agro-industry as well as the marine and fisheries sector. With the treatment of an island-based development system, the two KSN and NAL areas will be able to synergize with each other. Based on that, the pattern of regional development in terms of policy and the results of the Location Quontient statistical analysis, the concept of development can be applied to the concept of Maritime Economic Development